Photosynthetic performance and carbon metabolism in the ear organs of oats under drought stress - Fang, Jiaqi; Zhan, Yuan; Zhao, Baowen; Zhao, Yan; Chen, Youjun; Zhou, Qingping; Wang, Hui (Frontiers in Plant Science, 2025)
Sufficiently exploiting the potential of crop photosynthesis is one of the critical ways for improving cultivation production to face global climate change. In this study, oat plants were potted with three watering treatments. The glumes, lemmas, and flag leaves were sampled on days 0, 7, and 14 after the first floret blossomed under the control (denoted as CK-0, CK-7, and CK-14), drought stress (denoted as DS-7, and DS-14) and rewatering treatments (RW-14). Paraffin cross-section structures were observed, and the absolute water content, photosynthetic enzyme activities, carbohydrate content, dry matter weight, and total C and total N accumulation were determined in the glumes, lemmas and flag leaves. The results showed that stomatal tissues were present in both the inner and outer epidermis in the glumes and lemmas, and chloroplasts existed in the cells of both ear organs. Compared to CK-14, the absolute water content was significantly decreased in the flag leaves, stems, and seeds under DS-14, while drought stress did not significantly affect the water status of the glumes, lemmas, and peduncles. Drought stress significantly decreased the PEPC activities in the glumes, lemmas, and flag leaves, and the glumes had significantly higher PEPC activity than the flag leaves in the late stages of grain filling. Compared to CK-7, fructose and sucrose content was significantly decreased in the flag leaves under DS-7, while drought stress significantly increased the fructose, sucrose, and starch content in the glumes and lemmas. In addition, soluble sugar content was significantly increased in all glumes, lemmas, and flag leaves under drought stress. Rewatering significantly increased the carbohydrate content in the flag leaves, while it had no significant effect on the glumes and lemmas. As growth continued, the C and N contents and the dry matter mass in the seeds gradually increased, which was transferred from the glumes, lemmas, leaves, and stems. The results suggest that oats can tolerate a certain degree of drought without affecting the ears’ physiological function and yield, and ear organs can maintain water status and photosynthetic performance, which plays a major role in the maintenance of seed yield under drought stress conditions.